Recent developments in theoretical physics - Ghosh, Subir; Kar, Guruprasad (New Jersey, World Scientific, 2010)
This volume covers recent developments in the major areas of theoretical physics. The scope of the book ranges from small length scale (High Energy Physics, Neutrinos $1! =(B) through medium scale (Nuclear Physics) to large length scale (Condensed Matter Physics) up to classical and quantum Black Hole Physics. It also deals with topics in nonlinear physics, econophysics, new ideas in quantum mechanics, quantum information and quantum computation.s
Includes bibliographical references.
Keywords: Theoretical physics; Physics